Early Childhood Health During Conflict: The Legacy of the Lord's Resistance Army in Northern Uganda. (19th December 2021) - Bridges, Sarah; Scott, Douglas
Abstract: This paper finds evidence of severe health deficits among young children who were exposed to the Lord's Resistance Army insurgency in Northern Uganda (1987–2007). We employ a difference‐in‐differences approach to estimate a 0.74 standard deviation deficit in height‐for‐age z‐scores among children exposed to the fighting for a period of more than 9 months. Extending our analysis, we use a mediation model to investigate the transmission mechanisms through which the war may have affected childhood nutrition. We find support for the hypothesis that deficits occurred partly through changes in the frequency at which younger children received solid or semi‐solid foods.